Determination of electrokinetic and hydrodynamic parameters of proteins by modeling their electrophoretic mobilities through the electrically charged spherical porous particle - Deiber, Julio Alcides (2013)
This work explores the possibility of using the electrically charged "spherical porous particle" (SPP) to model the electrophoretic mobility of proteins in the low charge regime. In this regard, the electrophoretic mobility expression of the charged SPP (Hermans-Fujita model) is used and applied here to BSA and staphylococcal nuclease for different protocol pH values. The SPP is presented within the general framework of the "spherical soft particle" as described in the literature. The physicochemical conditions required to model proteins as SPP from their experimentally determined electrophoretic mobilities are established. It is shown that particle permeability and porosity and chain packing and friction fractal dimensions are relevant structural properties of proteins when hydrodynamic interaction between amino acid residues is present. The charge regulation phenomenon of BSA and staphylococcal nuclease with pIs ≈ 5.71 and 9.63, respectively, is described through the SPP within a wide range of bulk pH values. These case studies illustrate when the average regulating (pH) of the protein domain is lower and higher than the protocol pH. Further research for using the general spherical soft particle is also proposed on the basis of results and main conclusions.